Ampliação do tempo escolar: os desafios e as possibilidades no ensino fundamental da rede pública do município de Araguatins - Tocantins - Ferreira, Lucinalva (2015)
This work presents a study on full-time Education based on an analysis of the Programa Mais Educação (PMEd). The aim of this work is to analyze the impacts of public policy of expansion of the school time at the public elementary and junior high schools in Araguatins, Tocantins State, to evaluate the effectiveness of the proposal for the involved students at the studied schools. The full-time school program must complement the part-time school program in order to proportionate a full-time education to the students, providing them significant space and time and not just the same space and time that they had at the part-time school. In this perspective the problem to be investigated is presented: How the amplification of school time, through PMEd in public schools in Araguatins offers conditions to the effectiveness of a full-time education? From this question on we have define the general aim of this study: To analyze the impacts of the expansion of the school time at the elementary and junior high public schools of Araguatins, Tocantins State. The methodology is based on a study case in 4 elementary and junior high schools (two City schools and two State schools) in Araguatins. As research instruments we used documental research, questionnaires (for 24 teachers of the cited schools), semi-structured interviews (principals, pedagogic coordinators and Mais Educação program coordinators) and participant observations. For data analysis we have chosen content analysis. Through information from the researched professionals, we noticed that they recognize the importance of the expansion of school time and space for the students, as well as the educational support, diversified activities, parent support and local community partnership. However, there is yet a lot to learn to make that the full-time school promote a full-time education. We have verified that moments of continuing education for all the schools employees are fundamental. In this way, it is necessary to rethink the implementation of the real full-time school, with possibilities to discuss about this subject, in a way to satisfy the wants and the needs of the professionals, the students and the parents, therefore, to prepare critical and reflective citizens.